"How am I supposed to tell my mother what happened in today's class?" At the intersection between blended learning and design (thinking) education - Lehtonen, Miikka (Design and Technology Education: An International Journal, 2023)
Since the beginning of the 21st century, design education has been gaining momentum across disciplines as a means to equip students with skills relevant in the job market as well as to tackle wicked problems. One of the core assumptions behind integrating design education to other disciplines focuses on the need for hands-on and experiential opportunity exploration and collaborative learning, often prevalent in studio-based settings. However, as the Covid-19 pandemic has shown, physically accessing the campus or the studio is not always feasible, so how might this impact multidisciplinary design education? Acknowledging the notion that we no longer can take face-to-face learning for granted, this paper ask what aspects of design (thinking) education could be delivered in blended environments. I contribute to this body of knowledge by investigating students’ perceptions of their learning about design methods and processes in a problem-based blended learning course focusing on design and multidisciplinary teamwork. Visual learning diaries of forty-seven students were analyzed to better understand how blended learning can support or hinder learning about applying design to societal issues. Data analysis revealed three aspects – triggers for personal development, exploring ambiguity, and technology as providing structure – that form the concept learning frame. This concept sheds light on how the students perceived blended learning elements influencing their learning about how design could be applied to societal issues. Findings contribute to further dissolving the physical-digital dichotomy in design studio and education. Pedagogical implications focus on how blended learning can promote student agency in design education across disciplines.